Lunasin peptide promotes lysosome-mitochondrial mediated apoptosis and mitotic termination in MDA-MB-231 cells - Yuqiong Hao; Huimin Guo; Yechun Hong; Xin Fan; Yumei Su; Xiushi Yang; Guixing Ren (Food Science and Human Wellness)
Lunasin, a novel bioactive peptide, is well-known for its anti-proliferation activity. However, the mechanism of this effect is still poorly reported. Here, synthesized lunasin was used and its anti-proliferative function was observed at the concentration of 0.25 mg/mL in human breast cancer cell MDA-MB-231. Conjoint analysis of transcriptome and proteome of MDA-MB-231cells was further performed. The results demonstrated that cysteinyl aspartate specific proteinase (CASP) 3, CASP 7, and CASP 14 were significantly up-regulated after lunasin exposure, together with an increased Bax/Bcl-2 ratio from 22.9 to 210.6, which indicated that caspase-mediated mitochondria intrinsic apoptosis was highly activated. Moreover, lysosomal pathway was significantly suppressed under lunasin exposure, suggesting that lysosome may cooperate with mitochondria to participate in apoptosis. In addition, lunasin also down-regulated genes involved in DNA replication in MDA-MB-231 cells. Overall, our study reveals that the anti-proliferation effect of lunasin peptide might be triggered via the inhibition of DNA replication and cell mitosis, as well as the promotion of lysosome-mitochondrial mediated cell apoptosis.